Violence in Algerian Society and its Eradication between Reality and Challenge: The Case of Algerian School - Sahel, Malika; Mokrane, Fadila (European Journal of Social Science Education and Research, 2024)
Violence in Algerian society remains a serious social evil and a difficult reality that has attracted the attention of scholars, academicians and researchers from different Algerian towns. The focus of different  initial studies performed, mainly focused on the responsibility of the most important institutions concerned with the social  up growing and education, namely the family and the school towards the birth of violence and its eradication. Indeed, in the case one of these crucial institutions fails to perform its duties and assume its responsibility, violence becomes the language of the family with its members, of the school with all its different components; consequently the language of a whole society. On this basis, important questions impose themselves: what is the reality of violence in Algerian schools? And what are the appropriate measures that Algerians should take to reduce or eradicate it? Our analysis resulted in the necessity to review the duties of both the Algerian family and school, and some suggested strategies to reduce or eradicate school violence in the Algerian society.
Keywords: violence, school violence, social growth institutions, strategies